Eugeni la pelotari - Henao Toro, Félix; Salazar Patiño, Hernando (Manizales, Colombia : Editorial Universidad de Caldas, 2016)
"Eugeni la pelotari" is known as the first psychoanalytical novel in Spanish.
Online resource; title from PDF title page (Digitalia, viewed August 16, 2018)
Keywords: Men -- Spain -- Fiction; Psychological fiction; Urban fiction; Electronic books